Comparative Study: Distributing Fe Tablet and Fe Tablet Combined with Milk and Vitamin C - Badriah B; Omay Rohmana (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
The daily intake of iron (Fe) is needed to exchange the loss through feces, urine, and skin in the body. The basal loss is approximately around 14 μg / kg of body weight per day, or nearly equal to 0.08 mg of iron for female. Woman in childbearing age lose iron through menstrual periods. Some study have shown that the mean of blood loss during menstruation ranged between 25 to 30 cc per month. The amount of iron loss is about 12.5-15 mg per month or 0.4-0.5 mg per 28 days. If we combined it with basal loss, the total of iron loss is approximately 1.25 mg/day. If we calculated based on the frequency of menstrual blood loss distribution, 2.5 % of women need more than 2.4 mg iron per day. (E.M DeMaeyer, 1995). The aim of this study is to determine the difference between hemoglobin levels in Fe tablets and in the combination of Fe tablets with milk and vitamin C towards students. The experimental method with pre-test and post-test in control group was used in this study. The sample was divided into three groups, whereby group 1 was given Fe tablet and milk, group 2 was supplemented with combination of vitamin C, and the group 3 was given Fe tablet and mineral water. The respondents who were given Fe tablet + Milk had increased an average hemoglobin (Hb) level for about 1.5 mm/dl, respondents who were given Fe tablet + Vitamin C had increased an average hemoglobin (Hb) for about 1.3 mm/dl, and respondents who were given Fe + mineral water (control) had increased an average hemoglobin (Hb) for about 1.29 mm/dl. The proportion of respondents given Fe tablets + Milk is 21,1 %, Fe tablet + Vitamin C is 15.2%, and Fe tablet + mineral water is 15.1% . There is no significant differences among the treatment groups of Fe tablet + milk, Fe tablet + Vitamin C, and Fe tablet + mineral water. The value of the test is 0.0939 greater than 0.05. The consumption of Fe tablet can prevent anemia for students and improve the cross-sectoral cooperation in programing the distribution of Fe tablet itself, especially to female students in the school. Keywords: Fe tablets, milk, vitamin